2020
DOI: 10.1371/journal.pone.0227586
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the muscle-associated gene MYF6 in hairy cell leukemia

Abstract: Hairy cell leukemia (HCL) is a purine analog-responsive B-cell malignancy containing the BRAF V600E mutation, expressing CD22, CD11c, CD103, tartrate resistant acid phosphatase (TRAP) CD25, CD123, and annexin 1A. BRAF V600E and the latter 4 markers are usually absent in the more aggressive and chemoresistant variant HCLv. To evaluate differences between HCL and HCLv, expression microarrays comparing HCL with HCLv were performed for 24694 genes using 47323 probes. Microarray data from 35 HCL and 27 HCLv purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…Immunophenotyping reveals a HCL score < 3 with a typical lack of CD25 expression. We confirmed the decreased expression of ANXA1 (Annexin-1), and IL2RA (CD25) in vHCL (Swerdlow et al 2017 ), as well as the overexpression of TNFSRF13B (Arons et al 2020 ). In addition, we found that vHCL samples overexpressed the immune checkpoint regulators CD274 (PD-L1) and PDCD1LG2 (PD-L2) and underexpressed CD95 (FAS) receptor.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Immunophenotyping reveals a HCL score < 3 with a typical lack of CD25 expression. We confirmed the decreased expression of ANXA1 (Annexin-1), and IL2RA (CD25) in vHCL (Swerdlow et al 2017 ), as well as the overexpression of TNFSRF13B (Arons et al 2020 ). In addition, we found that vHCL samples overexpressed the immune checkpoint regulators CD274 (PD-L1) and PDCD1LG2 (PD-L2) and underexpressed CD95 (FAS) receptor.…”
Section: Discussionsupporting
confidence: 80%
“…Gene expression studies have extensively been performed in hematologic neoplasms and B cell lymphomas but few studies were published in HCL (Basso et al 2004 ; Arons et al 2020 ). As we had only unsorted white blood samples at our disposal, we used a special deconvolution algorithm which allowed us to select for B cell-specific genes despite the presence of contaminating other white blood cells in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Other mutated or deleted genes or regions in HCLv include CCND3, CCND1 (mutation and fusion with IgH), ATM, and 7p [ 6 , 52 , 72 , 73 ]. Myf6 is a muscle-associated gene found to be expressed in essentially 100% of HCL classic cases and much less frequently in HCLv or IGHV4-34+ HCL [ 74 ]. Unusual markers in classic HCL like CD38 have been associated with shorter time to progression and next treatment [ 75 ].…”
Section: How To Tell Hcl From Variantsmentioning
confidence: 99%
“…La mutation active la voie de signalisation MAPK/ERK, permettant la transcription des gènes de la famille ETS, FOS et MYC mais aussi de gènes inhibiteurs, notamment les DUSP (Dual Specificity Phosphatases) [49]. Des mutations autres que les mutations des gènes de la voie MAP-kinases (BRAF, MAP2K1) ont été identifiées: mutations des gènes du cycle cellulaire (CDKN1B dans 10-25%, beaucoup plus rarement TP53), mutations des gènes de la voie NF-kB (KLF2), mutations des gènes du spliceosome (U2AF1) ou des mutations des gènes régulateurs de l'épigénétique (KMT2C, EZH2, ARID1A, ARID1B, CREBP, KDM6A) [50][51][52][53][54]. Le rôle de ces différentes mutations dans la progression de la maladie reste à préciser [55].…”
Section: Mutation Braf V600eunclassified